Implementasi Transformasi Peran Pengawas Sekolah untuk Meningkatkan Kualitas Proses dan Hasil Belajar di Sekolah Dasar - Suprapti, Yuni; Subariyanti, Subariyanti; Supriyanto, Supriyanto (FKIP Universitas Wisnuwardhana, 2024)
The transformation of the role of school supervisors in accordance with the 2023 GTK Director General's Regulation aims,one of them is to improve the quality of learning processes and outcomes in elementary schools. The rationale for this policy lies in the need to strengthen academic and managerial supervision, as well as increase teacher competence in facing growing educational challenges. However, the implementation of this policy faces various problems, such as limited supervisory competence, limited resources, resistance to change, and limited supervisory time and personnel. Field data taken from a survey of 100 elementary school principals in Lawang and Singosari sub-districts, Malang district shows that 65% of them responded positively to this transformation, 20% felt that the policy was not optimal, and 15% were neutral. For reference This article refers to expert opinion and related journals, including the work of Sutopo and Munir (2020) on increasing the competence of school supervisors, as well as Arifin and Susanto (2022) which discusses the transformation of the role of supervisors in the digital era. Although there are challenges in implementation, the transformation of the role of school supervisors according to the 2023 Director General of GTK Regulation has significant potential to improve the quality of education in elementary schools in Indonesia.